Locusi, Illocusi, and Perlocusi Speech Acts in Ustad Hannan Attaki's Sharing Time event on the Youtube First Shof Media Indonesia Channel - Hikmah; Nurul Qomariyah (Demagogi: Journal of Social Sciences, Economics and Education, 2024)
In the current era, the use of YouTube media has increased very rapidly, this is because access is very easy. One of the YouTube content that is currently popular among the Muslim community is Ustad Hannan Attaki's sharing time content uploaded by the First Shof Media Indonesia Youtube Channel. This speech act also occurs in sharing time events, which can cover several topics ranging from questions about religious issues, mental health, to in-depth conversations with famous religious figures. In this study, researchers studied one of the sharing times with the sub-theme "Ever Tried Suicide But..." in terms of locutionary, illocutionary and perlocutionary speech. This research method uses a qualitative descriptive method by describing the dialogue conveyed by speakers and interlocutors. The Sharing Time event describes how events and speech acts are conveyed. Locutionary speech acts are in the form of statements and providing information. Iocution in the form of orders, confessions, etc. And perlocution has an impact on the behavior of the speaker and his interlocutor. All data produced is in the form of dialogue that corresponds to the three spoken words.